2023
DOI: 10.1021/jacs.3c05300
|View full text |Cite
|
Sign up to set email alerts
|

Thioamide Analogues of MHC I Antigen Peptides

Ruslan Gibadullin,
Rylie K. Morris,
Jiani Niu
et al.

Abstract: Short, synthetic peptides that are displayed by major histocompatibility complex I (MHC I) can stimulate CD8 T cells in vivo to destroy virus-infected or cancer cells. The development of such peptides as vaccines that provide protective immunity, however, is limited by rapid proteolytic degradation. Introduction of unnatural amino acid residues can suppress MHC I antigen proteolysis, but the modified peptides typically display lower affinity for MHC I and/or diminished ability to activate CD8 T cells relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 85 publications
(153 reference statements)
0
3
0
Order By: Relevance
“…Linear and macrocyclic peptide therapeutics derived from natural products often contain an extensive number of backbone-modifying npMs which can drastically improve peptide pharmacokinetics. ,, d -AAs are cleaved minimally or not at all by proteases, allowing for a significant increase in peptide stability. N -Alkylation of exposed secondary amine groups removes hydrogen bond donors, enhancing oral bioavailability and membrane permeability. Especially in macrocyclic peptides, conformationally constrained npMs such as cyclic β-AAs or cyclic γ-AAs can impart structural rigidity to allow for increased binding affinity . Heterocyclic, amide bond isosteres such as oxazoles, oxazolines, thiazoles, and thiazolines generally stabilize secondary structures and are less recognized by proteases, serving multiple purposes for increased peptide stability and membrane permeability. , One of the most notable natural products is the backbone macrocyclic peptide cyclosporin A, which contains two l -AAs with non-proteinogenic side chains, seven Me AAs, and one d -AA . These npMs contribute to the superior oral bioavailability and membrane permeability of cyclosporin A compared to other macrocyclic peptides …”
Section: Applications Of Polypeptides Containing Ribosomally Translat...mentioning
confidence: 99%
“…Linear and macrocyclic peptide therapeutics derived from natural products often contain an extensive number of backbone-modifying npMs which can drastically improve peptide pharmacokinetics. ,, d -AAs are cleaved minimally or not at all by proteases, allowing for a significant increase in peptide stability. N -Alkylation of exposed secondary amine groups removes hydrogen bond donors, enhancing oral bioavailability and membrane permeability. Especially in macrocyclic peptides, conformationally constrained npMs such as cyclic β-AAs or cyclic γ-AAs can impart structural rigidity to allow for increased binding affinity . Heterocyclic, amide bond isosteres such as oxazoles, oxazolines, thiazoles, and thiazolines generally stabilize secondary structures and are less recognized by proteases, serving multiple purposes for increased peptide stability and membrane permeability. , One of the most notable natural products is the backbone macrocyclic peptide cyclosporin A, which contains two l -AAs with non-proteinogenic side chains, seven Me AAs, and one d -AA . These npMs contribute to the superior oral bioavailability and membrane permeability of cyclosporin A compared to other macrocyclic peptides …”
Section: Applications Of Polypeptides Containing Ribosomally Translat...mentioning
confidence: 99%
“…The two latter mentioned issues can be circumvented by optimizing cleavage time and using anhydrous solvents [64b,65] . Because of these challenges, only few examples exist where multiple thioamides have been incorporated by SPPS [15d] …”
Section: Incorporation Of Thioamides Into Peptides and Proteinsmentioning
confidence: 99%
“…For example, Petersson and coworkers have shown that introduction of a single thioamide at a proteolysis hot spot increased the stability of the GLP1 hormone 750‐fold towards dipeptidyl peptidase [15c] . More recently, Gellman and coworkers have increased the half‐life of short T‐cell activating peptides by incorporating up to three thioamide bonds [15d] . Furthermore Petersson and coworkers have also studied the fluorescence quenching properties of thioamides and its usage to investigate proteases [15b,17] …”
Section: Introductionmentioning
confidence: 99%
“…Thioamide is a privileged structural skeleton in diverse bioactive molecules and a commonly encountered building block for thioheterocycle construction. , Particularly, thioamides, as bioisosteres of amides, exhibit excellent biological activity and improved stability to enzymatic hydrolysis . For example, upon replacement of the amide with a thioamide moiety, thiomyristoyl lysine remarkably increases its anticancer activity by up to 7000-fold compared to that of myristoyl lysine, and glucagon-like peptide 1-A S 8 (GLP-1-A S 8 ) possesses a half-life cycle period of 208 min, which is longer than that of the parent GLP-1 (1.9 min) (Scheme a) .…”
mentioning
confidence: 99%